ANALISIS PLAGIARISME PADA SKRIPSI MAHASISWA BIMBINGAN DAN KONSELING DENGAN JUDUL DISIPLIN BELAJAR DI UNIVERSITAS JAMBI - Yola Dwi Candri; Akmal Sutja; Dinny Rahmayanty (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research describes and explains the types of plagiarism in thesis writing of guidance and counseling students at Jambi University. Writing a thesis must avoid acts of plagiarism, whether intentionally or unintentionally. When writing a thesis, students often plagiarize word for word from sources that serve as references for writing the thesis. The aim of the research is to describe and explain the types of plagiarism that exist in Guidance and Counseling student theses which examine the concept of learning discipline. The type of research is literature. The sampling method is unit sampling. The samples in the research were 8 theses which examined the concept of learning discipline. Data collection was carried out by means of observation and documentation. From the analysis carried out on 8 student theses, the dominant guidance and counseling students at Jambi University committed verbatim plagiarism and plagiarism of sources in writing their thesis.